PENINGKATAN KESADARAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA SISWA KELAS 5 MI ASSHULAHA CIEURIH - Nasywa Zulfa Nujmatul Arifin (Kampus Akademik Publiser, 2026)
Clean and Healthy Living Behavior (PHBS) in the school environment is a crucial pillar in creating a conducive learning environment and maintaining student health from an early age. This activity aims to increase knowledge, awareness, and initiate changes in clean and healthy living behaviors among fifth-grade students at Asshulaha Islamic Elementary School. The implementation method uses an interactive educational approach combined with the screening of educational videos on PHBS indicators at school. This activity targets all 23 fifth-grade students at Asshulaha Islamic Elementary School. Evaluation of the activity's success was measured quantitatively through pre-tests and post-tests. The implementation results showed a significant difference in knowledge between before and after the intervention, as evidenced by the results of data analysis with a p-value of less than 0.05 ( < 0.05). The conclusion of this activity is that interactive education based on audiovisual media has been proven effective in increasing students' understanding of PHBS. Similar activities are recommended to be conducted periodically and supported by school policies to ensure the sustainability of these healthy living habits.